2001
DOI: 10.1007/s100380170119
|View full text |Cite
|
Sign up to set email alerts
|

IQGAP1, a negative regulator of cell-cell adhesion, is upregulated by gene amplification at 15q26 in gastric cancer cell lines HSC39 and 40A

Abstract: Our previous comparative genomic hybridization (CGH) study revealed a novel amplified region at 15q26 in two cell lines established from diffuse types of gastric cancer (GC). In this amplified region, FES and IGF1R, known targets on 15q26, were located telomeric to the amplicon in the two cell lines, HSC39 and 40A, suggesting that another tumor-associated gene exists in this region. While screening expressed sequence tags (ESTs) for novel genes in this region, we identified the IQGAP1 amplification. IQGAP1 has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 19 publications
1
47
0
Order By: Relevance
“…(15) Briefly, DpnII-restricted test and reference (male) genomic DNA were labeled by random priming with 0.2 mM each of dATP, dTTP and dGTP, 0.1 mM dCTP, and 0. 7), and denatured at 75°C for 10 min. After incubation at 37°C for 30 min, the mixture was applied to array slides set up in custom-made hybridization chambers, and incubated at 37°C on a slowly rocking table for 48-72 h. After hybridization, the slides were washed once in a solution of 50% formamide, 2 × SSC (pH 7.0) for 15 min at 50°C, once in 2 × SSC, 0.1% SDS for 15 min at 50°C, and once in a 0.1 mol/L sodium phosphate buffer containing 0.1% Nonidet P-40 (pH 8) for 15 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(15) Briefly, DpnII-restricted test and reference (male) genomic DNA were labeled by random priming with 0.2 mM each of dATP, dTTP and dGTP, 0.1 mM dCTP, and 0. 7), and denatured at 75°C for 10 min. After incubation at 37°C for 30 min, the mixture was applied to array slides set up in custom-made hybridization chambers, and incubated at 37°C on a slowly rocking table for 48-72 h. After hybridization, the slides were washed once in a solution of 50% formamide, 2 × SSC (pH 7.0) for 15 min at 50°C, once in 2 × SSC, 0.1% SDS for 15 min at 50°C, and once in a 0.1 mol/L sodium phosphate buffer containing 0.1% Nonidet P-40 (pH 8) for 15 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, our CGH experiments successfully identified several novel amplification targets, notably CD44 at 11p13 and IQGAP1 at 15q26. (6,7) However, techniques allowing more detailed detection and quantification of copy-number changes in GC should identify additional genes involved in gastric carcinogenesis, whose products could serve as diagnostic markers and/or therapeutic targets.…”
mentioning
confidence: 99%
“…The gene for IQGAP1 is located within a region of human chromosome 15 that is amplified in many gastric carcinomas [Pujana et al, 2001] and gastric tumor cell lines [Sugimoto et al, 2001]. Moreover, IQGAP1 protein is overexpressed in both the cell lines and the tumors [Sugimoto et al, 2001], and immunohistochemistry has demonstrated that in the tumors it is especially abundant in invasion fronts of metastatic cells [Nabeshima et al, 2002].…”
Section: Iqgapsmentioning
confidence: 99%
“…4 and 32 for recent reviews). IQGAP1 overexpression has also been detected in gastric and colorectal carcinomas and gastric cancer cell lines (35,41).…”
mentioning
confidence: 98%
“…4 and 32 for recent reviews). IQGAP1 overexpression has also been detected in gastric and colorectal carcinomas and gastric cancer cell lines (35,41).Less is known about the cellular distribution profiles and functions of IQGAP2, which was originally thought to be liver specific (5) but has since been localized in other cell types, including HCl-secreting gastric parietal cells (46) and blood platelets (39). Like IQGAP1, IQGAP2 binds to Cdc42 in its GTP-bound state and inhibits intrinsic and RhoGAP-stimulated GTP hydrolysis [although the nucleotide dependence of the interaction between IQGAP2 and Cdc42 is not as well established as for IQGAP1 (5,25,33,34)].…”
mentioning
confidence: 99%